Development of thermally stable and moldable chalcogenide glass for flexible infrared lenses. Issue 12 (30th May 2016) - Choi, Ju Hyeon; Cha, Du-Hwan; Kim, Jeong-Ho; Kim, Hye-Jeong
Abstract: Abstract : In this study, the ternary Ge–Sb–Se chalcogenide glass was fabricated by a standard melt-quenching technique for flexible infrared lenses. Chalcogenide glass should have unique thermal and mechanical properties to be applied to precision glass molding (PGM) process. Therefore, the relations between thermal properties and the moldability were investigated for (35–20)Ge–(5–20)Sb–60Se glass systems. The thermal and thermos-mechanical properties were characterized by the differential scanning calorimeter and thermos-mechanical analysis, respectively. Preceding experiments using a pressing tester were conducted before PGM process to evaluate the moldability. The surface condition of both chalcogenide glass disks and Tungsten Carbide (WC) molds were characterized by using an optical microscopy and an interferometer. The preferential compositions in (35–20)Ge–(5–20)Sb–60Se glass systems were selected to produce molded lenses. Finally, the molded chalcogenide lens was successfully fabricated using the preferential compositions and the processing conditions from the preceding experiments using a pressing tester.